HOW CONTINUOUS IMPROVEMENT METHODOLOGY – LEAN SIX SIGMA CAN INCREASE THE PRODUCTIVITY OF LOADING AND HAULING EQUIPMENT - Coutinho, Heitor Lobo; Pereira, Bruno Inácio; Pinto, Rodrigo José Lopes; de Lima, Hernani Mota; Costa, Leandro de Vilhena (Seven Editora, 2025)
The objective of this work is to increase the productivity of truck and excavator fleets using Lean Six Sigma methodology in the mine production process. The application of the Lean Six Sigma methodology has proven to be highly effective in several areas, for improving processes through the use of statistical tools for problem identification, cause analysis, optimization actions, resolution, sustainability and improvement of results, thus being a powerful methodology for companies seeking operational excellence and greater competitiveness. The fleet of excavators and trucks are the main equipment for material handling and production in the mine, in which through a case study it is possible to evidence the use of statistical tools in the development and identification of problems that affect productivity. In this case study, it is possible to demonstrate the application of all stages of the Lean Six Sigma methodology – DMAIC (Define, measure, analyse, improve, control), as a result of this project, it was possible to increase the overall productivity of the trucks of about 21% and an increase in the effective productivity of the excavators of around 31%, thus generating relevant financial gains estimated at R$ 4,502,141 per year and non-financial gains with improved safety conditions,  well-being of employees and reduction of carbon emissions by saving hours operated and diesel. The gain from reducing carbon emissions is estimated at 3,056 tons of carbon per year. In addition to the project's gains, the development of a culture of continuous improvement can be observed.DOI: https://doi.org/10.56238/sevened2024.037-141